Excited‐State Dynamics and Optical Properties of Silica Under Ultrafast Laser Irradiation - Tsaturyan, Arshak A.; Kachan, Elena; Stoian, Razvan; Colombier, Jean‐Philippe (Advanced Physics Research, 2025)
Excited by intense infrared ultrafast light pulses, a wide bandgap material undergoes nonlinear ionization, generating a high density of free electrons in conduction states. As a result, the electronic band structure is critically modified and the bandgap shrinks. This induces rapid changes in optical properties, dramatically affecting the absorption spectrum during light coupling to the dielectric surface or during nonlinear propagation inside the bulk. This study analyzes the structural behavior and the modification of the optical properties of laser‐excited silica glass at the molecular cluster level through first‐principles simulations. Employing density functional theory and the GW approximations for band structure under nonequilibrium conditions, alongside the Bethe–Salpeter equation, the dynamics of the optical properties of fused silica are comprehensively explored. The behavior of excited fused silica in a wide photon energy range (from a few to 20 eV) is thus predicted. Laser‐induced electron excitation triggers a redistribution of charges between oxygen and silicon atoms, accompanied by a significant increase in electronic pressure, local atomic structure rearrangement, and material expansion. Molecular dynamics simulations offer a temporal perspective on the excited state dynamics, unveiling the intricate interplay between electronic and atomic effects on bandgap evolution. The analysis sheds light on excitonic resonances, intraband and interband transitions in fused silica under ultrafast laser irradiation, providing valuable insights into its excited state behavior and optical properties. Calculations of optical properties of fused silica irradiated by ultrafast laser pulse. The contribution of both electronic and atomic factors to bandgap narrowing is estimated using density functional theory and GW approaches. The dielectric function Im[ε(ω)] is evaluated within the framework of the Bethe–Salpeter equation approximation and Drude model.